Efektivitas Model Pembelajaran Berbasis Proyek Terhadap Kemampuan Kolaborasi dan Literasi Lingkungan Siswa SMP pada Materi Ekosistem - Isnaini Rahmah Lubis; Ummi Nur Afinni Dwi Jayanti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to examine the effectiveness of the project-based learning (PjBL) model in improving students’ collaboration skills and environmental literacy in ecosystem topics. The method used was a quasi-experimental design with a one-group pretest-posttest involving 32 seventh-grade students at SMP Negeri 2 Perbaungan. Research instruments consisted of observation sheets and an environmental literacy test that had been validated and tested for reliability. The results indicate that the implementation of PjBL successfully enhanced students’ collaboration skills and environmental literacy in cognitive, affective, and behavioral aspects. In conclusion, project-based learning is effective in developing collaboration and environmental literacy, as well as fostering students’ awareness and responsibility toward the environment. Keywords: Collaboration, Environmental Literacy, Project-Based Learning